The correlation between hemostatic blood parameters and sepsis in patients with gunshot wounds referred to a training and research hospital. - Can, Derya; Eryılmaz, Mehmet (Turkish Journal of Trauma & Emergency Surgery / Ulusal Travma ve Acil Cerrahi Dergisi, 2023)
BACKGROUND: War injuries are different among the causes of trauma compared to cases in normal life. Patients with multi-trauma due to war injury are prone to develop infective complications such as sepsis or septic shock. Septic complications are one of the leading causes of late death in multi-trauma patients. Prompt, appropriate, and effective management of sepsis has been shown to prevent multiorgan dysfunction and improve mortality and clinical outcomes. However, there is no ideal biomarker to predict sepsis. The aim of this study was to determine whether there is a correlation between hemostatic blood parameters and sepsis in patients with gunshot wounds (GSW). METHODS: This descriptive study was conducted as a retrospective analysis of patients who were referred to the adult emergency department of a training and research hospital between October 1, 2016, and December 31, 2017, with a diagnosis of GSW and who developed sepsis (n=56) and did not develop sepsis (n=56) during follow-up. Demographic data such as age, sex, and blood parameters obtained from the hospital information system in the emergency department were recorded for each case. The statistical difference in hemostatic blood parameters between the two groups with and without sepsis was evaluated with Statistical Package for the Social Sciences 20.0 program. RESULTS: The mean age of the patients was 26.9±6.67. All of the patients were male. Of the patients who developed sepsis, 57% (n=32) were injured with improvised explosive devices (IEDs), 30% (n=17) were injured with firearms and when the anatomical injury sites were analyzed, 64% (n=36) had multiple injuries. In patients who did not develop sepsis, 48% (n=27) had IED, 43% (n=24) had GSW and 48% (n=27) had multiple injuries and 32% (n=18) had extremity injuries. Among the hemostatic blood parameters, platelet count (PLT), PTZ, INR, and Ca values showed a statistically significant difference between patients with and without sepsis, and when analyzed with the receiver operating characteristics curve, PTZ and INR showed the best diagnostic performance compared to the tested values. CONCLUSION: Increased PTZ and INR values and decreased Ca and PLT values in patients with GSW may alert clinicians to sepsis and direct them to initiate or change antibiotic therapy.